2006
DOI: 10.1186/1745-0179-2-24
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundA number of studies have suggested a link between the patient's psyche and the course of inflammatory bowel disease (IBD). Although pharmacotherapy with antidepressants has not been widely explored, some investigators have proposed that treating psychological co-morbidities with antidepressants may help to control disease activity. To date a systematic analysis of the available studies assessing the efficacy of antidepressants for the control of somatic symptoms in IBD patients has not been performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(38 citation statements)
references
References 41 publications
(41 reference statements)
0
38
0
Order By: Relevance
“…82 Recent consensus guidelines for CD management include recommendations to assess for anxiety and depression and identify appropriate treatment if needed. 83 The concerns about psychiatric impact and need for intervention have been recognized in other chronic illness populations as well, with recent advisories recommending routine screening for depression for those with heart disease or diabetes.…”
Section: Managing Comorbid Anxiety and Depression In Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…82 Recent consensus guidelines for CD management include recommendations to assess for anxiety and depression and identify appropriate treatment if needed. 83 The concerns about psychiatric impact and need for intervention have been recognized in other chronic illness populations as well, with recent advisories recommending routine screening for depression for those with heart disease or diabetes.…”
Section: Managing Comorbid Anxiety and Depression In Ibdmentioning
confidence: 99%
“…82 Based on the available literature, including an open-label study and six case reports, it was found that the targeted anxiety or depression in IBD patients was generally responsive to pharmacological treatment. In addition, there was a positive effect on disease activity in the majority of the reports, which primarily involved use of the antidepressants paroxetine or buproprion.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…The SSRI and SNRI medications are secondgeneration antidepressants that have been well established in the literature as being similarly effective for anxiety and depression [54] . In humans, it has been observed that although antidepressants improve both the mental and somatic status of IBD patients, the low quality of available research provides significant barriers to making a definitive statement on their efficacy or lack thereof [55] . Animal models, however, have found a positive impact of desipramine and fluoxetine on inflammation in models of IBD.…”
Section: Psychiatric Therapy In Ibdmentioning
confidence: 99%
“…Amitriptyline is an antidepressant drug that is widely used for the treatment of IBD and gastrointestinal disorders [55,63] . It is effective for treating psychological and somatic symptoms in patients suffering from IBD [55] .…”
Section: Psychiatric Therapy In Ibdmentioning
confidence: 99%
See 1 more Smart Citation